2016
DOI: 10.1158/0008-5472.can-15-1484
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogen Suppresses Efflux of the Diagnostic Marker Protoporphyrin IX in Lung Carcinoma

Abstract: One promising method to visualize cancer cells is based on the detection of the fluorescent photosensitizer protoporphyrin IX (PpIX) synthesized from 5-aminolevulinic acid (ALA), but this method cannot be used in cancers that exhibit poor PpIX accumulation. PpIX appears to be pumped out of cancer cells by the ABC transporter G2 (ABCG2), which is associated with multidrug resistance. Genistein is a phytoestrogen that appears to competitively inhibit ABCG2 activity. Therefore, we investigated whether genistein c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Another kinase inhibitor gefitinib was found to increase intracellular PpIX and cytotoxicity induced by ALA-PDT in human glioma cell lines (26). Genistein, a kinase inhibitor and isoflavone phytoestrogen, has recently been shown to increase ALA-PpIX in a lung cancer tumor model (27) and human glioma cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Another kinase inhibitor gefitinib was found to increase intracellular PpIX and cytotoxicity induced by ALA-PDT in human glioma cell lines (26). Genistein, a kinase inhibitor and isoflavone phytoestrogen, has recently been shown to increase ALA-PpIX in a lung cancer tumor model (27) and human glioma cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…A separate study demonstrated the use of genistein, a phytoestrogen that appears to competitively inhibit ABCG2 for the enhancement of ALA-induced PpIX accumulation [177]. This study showed that genistein promoted the accumulation of PpIX in A549 cell lines both in vitro and in vivo by preventing ABCG2-mediated PpIX efflux and upregulating the gene expression of heme synthesis enzymes.…”
Section: Abcg2 Knockdown By Rnaimentioning
confidence: 85%
“…Estrogen-depleted rats were found to reduce ALA-induced PpIX levels in their tumors suggesting that estrogen and the phytoestrogen genistein may accelerate the accumulation of PpIX via ERβ signaling. This study reported that ALA-induced PpIX accumulation was increased by 3.7 times in vitro and 1.8 times in vivo, following pre-treatment with genistein [177]. Although PpIX was found to selectively accumulate in tumors [164], ALA-based PDD and PDT remained unsatisfactory in diagnosing some tumors that accumulate insufficient amounts of PpIX.…”
Section: Abcg2 Knockdown By Rnaimentioning
confidence: 94%
“…Other studies have similarly shown that the efficacy of PDT with various photosensitizers has a clear correlation with their fluorescence intensity [ 11 , 25 ]. Overexpression of adenosine triphosphate-binding cassette (ABC) efflux transporters, such as ABCB1 (multidrug resistance protein 1 (MDR1)/permeability glycoprotein (P-gp)), ABCC1 (multidrug resistance-associated protein 1 (MRP1)) and breast cancer resistance protein ABCG2 (BCRP), is a key factor in PDT resistance in colon adenocarcinoma and lung carcinoma cells [ 14 , 20 , 51 ]. P-gp and BCRP are highly expressed in HepG2 cells [ 10 , 24 ], which may be related to lower accumulation of Ptpp in these cells compared to NOZ cells.…”
Section: Discussionmentioning
confidence: 99%